2022
DOI: 10.1371/journal.pone.0262965
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of the Perinatal Bereavement Care Confidence Scale (C-PBCCS) in nursing practice

Abstract: Background The Perinatal Bereavement Care Confidence Scale (PBCCS) was designed to evaluate midwives’ and nurses’ confidence and its psychosocial factors to provide bereavement care in Ireland. However, it is unknown whether this scale is valid and reliable for use with midwives and nurses in China. The aim of this study was to translate the English version into Chinese (C-PBCCS) and determine its validity and reliability in a population of Chinese midwives and nurses. Methods In this cross-sectional observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…At present, there is no routine emotional support for the women and obstetric nursing staff in China. The majority of nurses and midwives had not received training in perinatal bereavement care (85.2%) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no routine emotional support for the women and obstetric nursing staff in China. The majority of nurses and midwives had not received training in perinatal bereavement care (85.2%) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Cronbach's α coe cient and the split-half coe cient were used to verify the internal reliability. The results showed that Cronbach's α coe cient and split-half coe cient of scale were above reference, indicating that the scale has an excellent internal consistency according to the standard classi cation recommendation [48,49]. The result showed that the re-test coe cient of the scale was exceeded the suggested value, meaning the scale has the capability for obtaining a stable result under similar external conditions and has acceptable external reliability [50].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese nursing staff are unfamiliar with how to provide high-quality perinatal bereavement care. It is reported that the majority of Chinese nurses and midwives had not received training in perinatal bereavement care (85.2%) 47. Therefore, it has become an urgent problem to construct the PBCTP preparing competent nurses and midwives to provide this special care in the context of China.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the majority of Chinese nurses and midwives had not received training in perinatal bereavement care (85.2%). 47 Therefore, it has become an urgent problem to construct the PBCTP preparing competent nurses and midwives to provide this special care in the context of China. Although a series of PBCTPs have been designed and conducted, [60][61][62][63] the lack of a theoretical basis, long-term follow-ups, valid and reliable evaluation tools and comprehensive training contents were the main deficiencies of the existing education programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation